Relationship between sources of counseling self-efficacy and counseling self-efficacy among Malaysian school counselors - Ooi, Pei Boon *; Wan Marzuki Wan Jaafar; Maznah Baba (Elsevier for Western Social Science Association, 2017)
School counselors’ role in the formation and transformation of the Malaysian educationsystem is indispensable. This study employs the Social Cognitive Theory to examine therelationship between the sources of counseling self-efficacy and the Malaysian school coun-selors’ counseling self-efficacy. The Sources of Counseling Self-Efficacy questionnaire andthe Counseling Self-Estimate Inventory were used on 541 school counselors nationwide,as the respondents. The result reveals mastery experience has the strongest relationshipwith counseling self-efficacy. Recommendations on how to strengthen self-efficacy areproposed.